Sex cult nun: breaking away from the Children of God, a wild, radical religious cult - Jones, Faith (William Morrow, an imprint of HarperCollins Publishers, 2021)
Inhaltsverzeichnis: A (not so brief) history of my family and the Children of God -- The great escape! -- Watch out for snakes -- It takes a village -- Don't work for money, honey -- Train up a child -- Heavenly houris -- A change in attitude -- My sister is a Jesus baby -- Farm life -- Burn after reading -- It's a teen revolution! -- The silent coup -- The grand experiment -- Suffering makes you bitter or better -- The land of much too much -- The new kid in the class -- Gentling and breaking -- Education is power -- Breaking the rules -- All for one means none for you -- Long live the Prophet -- Meeting the prince -- The breaking -- Pretending is the first step to being -- The big decision -- Suffering is never godly -- On my own -- Knowledge and truth -- Never give up -- The truth will set you free -- Epilogue: I own me.